Cortical and Subcortical Dysmetabolism Are Dynamic Markers of Clinical Disability and Course in Anti-LGI1 Encephalitis. Issue 2 (March 2022) - Rissanen, Eero; Carter, Kelsey; Cicero, Steven; Ficke, John; Kijewski, Marie; Park, Mi-Ae; Kijewski, Joseph; Stern, Emily; Chitnis, Tanuja; Silbersweig, David; Weiner, Howard L.; Kim, Chun K.; et al.
Abstract : Background and Objectives: This [ 18 F]fluorodeoxyglucose (FDG) PET study evaluates the accuracy of semiquantitative measurement of putaminal hypermetabolism in identifying anti–leucine-rich, glioma–inactivated-1 (LGI1) protein autoimmune encephalitis (AE). In addition, the extent of brain dysmetabolism, their association with clinical outcomes, and longitudinal metabolic changes after immunotherapy in LGI1-AE are examined. Methods: FDG-PET scans from 49 age-matched and sex-matched subjects (13 in LGI1-AE group, 15 in non–LGI1-AE group, 11 with Alzheimer disease [AD], and 10 negative controls [NCs]) and follow-up scans from 8 patients with LGI1 AE on a median 6 months after immunotherapy were analyzed. Putaminal standardized uptake value ratios (SUVRs) normalized to global brain (P-SUVRg), thalamus (P/Th), and midbrain (P/Mi) were evaluated for diagnostic accuracy. SUVRg was applied for all other analyses. Results: P-SUVRg, P/Th, and P/Mi were higher in LGI1-AE group than in non–LGI1-AE group, AD group, and NCs (all p < 0.05). P/Mi and P-SUVRg differentiated LGI1-AE group robustly from other groups (areas under the curve 0.84–0.99). Mediotemporal lobe (MTL) SUVRg was increased in both LGI1-AE and non–LGI1-AE groups when compared with NCs (both p < 0.05). SUVRg was decreased in several frontoparietal regions and increased in pallidum, caudate, pons, olfactory, and inferior occipital gyrus in LGI1-AE group when compared with that in NCs (all p < 0.05). In LGI1-AE group, both MTL and putaminal hypermetabolism were reduced after immunotherapy. Normalization of regional cortical dysmetabolism associated with clinical improvement at the 6- and 20-month follow-up. Discussion: Semiquantitative measurement of putaminal hypermetabolism with FDG-PET may be used to distinguish LGI1-AE from other pathologies. Metabolic abnormalities in LGI1-AE extend beyond putamen and MTL into other subcortical and cortical regions. FDG-PET may be used in evaluating disease evolution in LGI1-AE. Classification of Evidence: This study provides Class II evidence that semiquantitative measures of putaminal metabolism on PET can differentiate patients with LGI1-AE from patients without LGI1-AE, patients with AD, or NCs.